Analytical modeling of subthreshold current and subthreshold swing of Gaussian-doped strained-Si-on-insulator MOSFETs - Rawat G.; Kumar S.; Goel E.; Kumar M.; Dubey S.; Jit S. (My University, 2025)
This paper presents the analytical modeling of subthreshold current and subthreshold swing of shortchannel fully-depleted (FD) strained-Si-on-insulator (SSOI) MOSFETs having vertical Gaussian-like doping profile in the channel. The subthreshold current and subthreshold swing have been derived using the parabolic approximation method. In addition to the effect of strain on silicon layer, various other device parameters such as channel length (L/, gate-oxide thickness .tox/, strained-Si channel thickness .ts-Si/, peak doping concentration .NP/, project range .Rp/ and straggle .δ p/ of the Gaussian profile have been considered while predicting the device characteristics. The present work may help to overcome the degradation in subthreshold characteristics with strain engineering. These subthreshold current and swing models provide valuable information for strained-Si MOSFET design. Accuracy of the proposed models is verified using the commercially available ATLAS™, a two-dimensional (2D) device simulator from SILVACO. © 2014 Chinese Institute of Electronics.